2015
DOI: 10.1161/circgenetics.114.000974
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 2–Dependent Arrhythmogenic Cardiomyopathy Is Caused by a Loss of Adhesive Function

Abstract: Background— The desmosomal cadherin desmoglein 2 (Dsg2) localizes to the intercalated disc coupling adjacent cardiomyocytes. Desmoglein 2 gene ( DSG2 ) mutations cause arrhythmogenic cardiomyopathy (AC) in human and transgenic mice. AC is characterized by arrhythmia, cardiodilation, cardiomyocyte necrosis with replacement fibrosis, interstitial fibrosis, and intercalated disc dissociation. The genetic DSG2 constellations encount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 48 publications
6
81
0
Order By: Relevance
“…Several mouse models have been developed for Dsg2 [15, 2022, 36], Jup [12, 23, 13, 37], Pkp2 [16, 24, 38], Dsp [17] and Des [39] showing either early embryonic lethality or different cardiac pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several mouse models have been developed for Dsg2 [15, 2022, 36], Jup [12, 23, 13, 37], Pkp2 [16, 24, 38], Dsp [17] and Des [39] showing either early embryonic lethality or different cardiac pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The global knock-out of Dsg 2 is embryonically lethal [15] whereas the cardiac specific knock-out of Dsg2 causes severe cardiomyopathy [22]. In contrast, transgenic mice overexpressing cardiac Dsg2 are without an obvious phenotype [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A separate study on chicken embryos indicates that RBFox3, one of the three isoforms of the RBFox family, is ubiquitinated and degraded in proteasome‐dependent manner, which may further affect the localization and functioning of other isoform RBFox2 . Desmoglein‐2 acts as linker proteins adhering adjacent cardiomyocytes; a missense mutation or cardiac‐specific ablation of this protein is associated with arrhythmogenic cardiomyopathy and familial dilated cardiomyopathy . It was observed that cardiac fibrosis associated protein galectin‐3 plays important roles in stabilizing desmoglein‐2, by interfering with its degradation in proteasome …”
Section: Proteasomal System: Failure May Drive Onset Of Several Diseasesmentioning
confidence: 99%